Mayas in the Marketplace Tourism, Globalization, and Cultural Identity - Little, Walter E. (University of Texas Press, 2021)
Selling handicrafts to tourists has brought the Maya peoples of Guatemala into the world market. Vendors from rural communities now offer their wares to more than 500,000 international tourists annually in the marketplaces of larger cities such as Antigua, Guatemala City, Panajachel, and Chichicastenango. Like businesspeople anywhere, Maya artisans analyze the desires and needs of their customers and shape their products to meet the demands of the market. But how has adapting to the global marketplace reciprocally shaped the identity and cultural practices of the Maya peoples? Drawing on over a decade of fieldwork, Walter Little presents the first ethnographic study of Maya handicraft vendors in the international marketplace. Focusing on Kaqchikel Mayas who commute to Antigua to sell their goods, he explores three significant issues: how the tourist marketplace conflates global and local distinctions. how the marketplace becomes a border zone where national and international, developed and underdeveloped, and indigenous and non-indigenous come together. how marketing to tourists changes social roles, gender relationships, and ethnic identity in the vendors' home communities. Little's wide-ranging research challenges our current understanding of tourism's negative impact on indigenous communities. He demonstrates that the Maya are maintaining a specific, community-based sense of Maya identity, even as they commodify their culture for tourist consumption in the world market